Pantang Larang in The Sepinggan Village Muslim Community from The Perspective of Character Education - Syamsul Kurniawan (Ta'dib: Jurnal Pendidikan Islam, 2016)
The focus of this research is on pantang larang (taboos or superstitions in Malay culture) which serves as local wisdom of the Muslim community in Sepinggan village. It is examined from the perspective of character education. As previous research  indicates that the Muslim community in this area has a lot of local wisdom which includes values or a set of unwritten rules about behavior and  interaction between  individuals in daily life. Among them is pantang larang which contains values or moral message, especially in the context of relationship with God, with oneself and with other creatures of God, that should be manifested in thoughts, attitudes, feelings, words and deeds so as to correspond to norms, manners, and adat (customs). In other words, the Sepinggan Village Muslim community uses pantang larang as a medium as a basis for character building.Fokus penelitian ini adalah pantang larang (tabu atau takhayul dalam budaya Melayu) yang berfungsi sebagai kearifan lokal dari komunitas Muslim di desa Sepinggan. Hal ini diteliti dari perspektif pendidikan karakter. Seperti penelitian sebelumnya menunjukkan bahwa komunitas Muslim di daerah ini memiliki banyak kearifan lokal yang mencakup nilai-nilai atau seperangkat aturan tidak tertulis tentang perilaku dan interaksi antar individu dalam kehidupan sehari-hari. Di antaranya adalah pantang larang yang berisi nilai-nilai atau pesan moral, terutama dalam konteks hubungan dengan Tuhan, dengan diri sendiri dan dengan makhluk Allah lainnya, yang harus diwujudkan dalam pikiran, sikap, perasaan, perkataan dan perbuatan sehingga sesuai dengan norma-norma, sopan santun, dan adat (kebiasaan). Dengan kata lain, masyarakat Muslim Desa Sepinggan menggunakan pantang larang sebagai media sebagai dasar untuk membangun karakter.